Prevalence of Vitamin D Deficiency and Its Associated Disorders at a Tertiary Care Hospital of The Al Qassim Region of Saudi Arabia - Mohammad Jawaid Arif; Sanjay Kumar Gupta; Fahd Al Khalifah (Medsci Publications, 2017)
Introduction: Vitamin D is a fat-soluble vitamins which is very important for maintaining healthy bone and essential for calcium and phosphorus homeostasis. This study was conducted to find out the prevalence of vitamin D deficiency and associated disorders among patients admitted in the medical ward and associated diseases/disorders if any. Methods: It was a hospital based retrospective study. Results: Total 144 (75%) of patients had vitamin D deficiency. The most common symptom among patients due to vitamin D deficiency was joint pain (46%). The common disease associated with vitamin D deficiency patients was diabetes (28%) which was significantly associated (p<0.05). Vitamin D level and patient's height were significantly associated with each other (t = 126.36, P<0.0001). Linear regression model shows significant relationship between the body mass index of the patients and their serum cholecalciferol (Vitamin- D3) level (t=10.37, P<0.05) and 95% (Constant 15.64) confidence interval level of coefficient 12.6 -18.6. Conclusion: The study showed vitamin D deficiency was the major problem of the area , more in younger age group and common among female patients. The obesity also one of the major problem of the patients of study group and Vitamin D and calcium deficiency significantly associated with obesity.